Hemodialysis catheter-related bloodstream infections: a single-center experience - Mohan V Bhojaraja; Ravindra Attur Prabhu; Shankar Prasad Nagaraju; Indu Ramachandra Rao; Srinivas Vinayak Shenoy; Dharshan Rangaswamy; Veena Natti Krishna; Megha Nagaraj Nayak (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: In hemodialysis (HD) patients, catheter-related bloodstream infections (CRBSI) cause significant morbidity and mortality. Objectives: We analyzed dialysis CRBSI incidence, associated factors, and the spectrum of the causative organisms. Patients and Methods: Patients aged ≥18 years either on maintenance HD or with acute kidney injury having CRBSI (NKF-KDOQI criteria) were included in this prospective observational study and patients with other infections were excluded. Blood, catheter tip culture, and antibiogram were analyzed. All patients were initially treated with antibiotics covering both gram-positive and gram-negative pathogens. Results: Of 921 catheters (882 patients) included, 212 (23%) had CRBSI, of which 69(32.5%) and 143 (67.5%) had culture-positive probable CRBSI and culture-negative possible CRBSI respectively. 131 (61.8%) were <60 years, 133 (62.7%) were males, 177 (83.5%) had diabetes, 141 (66.5%) had leukocytosis and 172(81.1%) had positive procalcitonin. In addition, 193 (91%) had uncuffed catheters and 162 (76.4%) had jugular catheters. Our study showed a CRBSI incidence of 13.39/1000 catheter days, median catheter days, and median time to CRBSI was 40 and 17.2 days respectively. 41 (19.3%) catheters were salvaged (with antibiotic administration or guidewire exchange) and 42 (19.8%) had exit site infection. Gram-positive coagulase-negative Staphylococcus aureus (CoNS) (n=31; 44.9%) followed by extended-spectrum beta-lactamase (ESBL) enteric gram-negative organisms (n=30; 43.4%) were common isolates and remaining had fungal etiology (n=8; 11.7%). In our study, the mortality rate was 6.6% (n=14). Conclusion: The incidence of CRBSI was high in our population. In culture-positive cases, gram-positive organisms contributed marginally higher than gram-negative organisms. CoNS and ESBL enteric gram-negative organisms are the commonest isolates. More than two-thirds of patients with CRBSI had diabetes mellitus and leukocytosis at presentation.